2005
DOI: 10.3748/wjg.v11.i22.3479
|View full text |Cite
|
Sign up to set email alerts
|

Rat bone marrow mesenchymal stem cells differentiate into hepatocytesin vitro

Abstract: The method combining gradient density centrifugation with plastic adherence can isolate MSCs. Rat MSCs may be differentiated into hepatocytes by FGF-4 and HGF. Cytokines may play a more important role in differentiation from rat MSCs into hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 31 publications
3
30
0
3
Order By: Relevance
“…Schwartz et al [14] . and Kang et al [15] . reported that FGF-4 and HGF could induce differentiation of bone marrow MSCs into functional hepatocyte-like cells.…”
Section: The Extensive Characterization Of These Cells Has Revealedmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwartz et al [14] . and Kang et al [15] . reported that FGF-4 and HGF could induce differentiation of bone marrow MSCs into functional hepatocyte-like cells.…”
Section: The Extensive Characterization Of These Cells Has Revealedmentioning
confidence: 99%
“…It has been reported that bone marrowderived MSCs can differentiate into mesoderm cells such as osteoblasts [1][2][3] , adipocytes [4][5][6] , neural and brain cells [7][8][9][10] ,cardiomyocytes [11][12][13] and hepatocytes [14,15] in vivo or in vitro. However, it has been demonstrated that the number and the differentiating potential of bone marrow MSCs decrease with age [16].…”
Section: Introductionmentioning
confidence: 99%
“…One medium (medium A) was supplemented with hepatocyte growth factor (HGF), a mesenchymally derived potent mitogen for parenchymal hepatocyte cells which acts via the HGF receptor c-MET, a transmembrane tyrosine kinase protein [Schaffler and Buchler, 2007]. As is well known, stem cells derived from human liver and rat bone marrow differentiate in mature hepatocytes when cultured in vitro in the presence of HGF and fibroblast growth factor 4, as indicated by the expression of functional cytochrome P450, albumin and urea production [Kang et al, 2005;Herrera et al, 2006]. In the second procedure, the me dium (medium B) was supplemented with oncostatin M (OSM), basic fibroblast growth factor (bFGF) and dimethyl sulfoxide (DMSO).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these approaches used toxic models, in which the intrinsic selfrenewing capacity of the recipient liver was suppressed (Dahlke, 2003, Kang, 2005. Di Bonzo observed only 0,2% human hepatocytes after transplantation of human MSC into immunodeficient mice with chronic liver injury (Di Bonzo, 2008).…”
Section: Functional Liver Remnant Volumementioning
confidence: 99%